Comparative Genomics of an Emerging Multidrug-Resistant blaNDM-Carrying ST182 Lineage in Enterobacter cloacae Complex - Angeliki Mavroidi; Elisavet Froukala; Athanasios Tsakris (MDPI AG, 2024)
Background: Enterobacter cloacae, E. hormaechei and related subspecies remain the most clinically relevant among the Enterobacter cloacae complex (ECC). Carbapenemase-producing ECC strains are increasingly identified in hospital-acquired infections and usually belong to four main multilocus sequence types (MLST STs) named ST114, ST93, ST90 and ST78. Instead, ST182 has been sporadically reported among E. hormaechei strains, and recently, outbreaks of blaNDM-producing ST182 clonal strains have emerged. Herein, we aimed to investigate the presence of ST182 and explore its evolution and modes of blaNDM acquisition. Methods: A phylogenetic analysis of 646 MLST STs identified among 4685 E. hormaechei whole-genome sequencing (WGS) assemblies deposited in public repositories was performed, as well as an in silico comparative and phylogenomic analyses for 55 WGS assemblies of ST182. blaNDM-harboring contigs were also compared to published plasmid sequences. Results: ST182 E. hormaechei strains were recovered from patients on five continents during 2011-2021. They were divided into three major genomic clusters, comprising a separate clonal complex with six other STs. In 30 out of 55 ST182 WGS assemblies, blaNDM-harboring structures were identified that were similar to the plasmids predominant in Gram-negative bacteria, harboring resistance genes to multiple antibiotic classes and virulence genes. No associations between the genomic clusters and the country/continent of isolation or the presence and the plasmid types of the blaNDM-harboring contigs were observed. Conclusions: Our findings show that ST182 E. hormaechei strains have been identified in the past decade worldwide; 54.5% of them carried diverse blaNDM genetic structures, suggesting recent acquisition of the blaNDM alleles. Thus, blaNDM-harboring ST182 is an emerging multidrug-resistant and virulent lineage in ECC strains that requires close monitoring.